Building Engagement: A Canva-Driven Interactive Media for Fourth-Grade Science and Social Studies Learning - Alifah Septianingrum; Safitri Yosita Ratri (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2025)
This study aimed to develop and validate a Canva-driven interactive website designed to enhance student engagement in fourth-grade Science and Social Studies (IPAS) learning, specifically on the topic of Energy Transformation. Employing the Research and Development (R&D) method with the systematic ADDIE model, the research was conducted at SD N Karanganyar, Gunungkidul, involving a classroom teacher and 19 students. Data collection included expert validation, student and teacher questionnaires, and field trials to evaluate the media’s feasibility and impact on learning involvement. The developed interactive website integrates contextual illustrations, animations, and embedded quizzes to support conceptual understanding. Validation results from material and media experts confirmed high feasibility in terms of content accuracy, visual design, and interactivity. Classroom implementation revealed that the Canva-based media effectively fostered active engagement, increased motivation, and improved comprehension of abstract concepts, as reported by both students and the teacher. The findings affirm that strategically designed, Canva-driven interactive media serves as both a feasible and effective instructional tool for building meaningful engagement in elementary IPAS education, aligning with the student-centered and dynamic learning goals of the Merdeka Curriculum.